1959
DOI: 10.1111/j.1476-5381.1959.tb01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Lethal Organophosphate Poisoning by Quaternary Pyridine Aldoximes

Abstract: The effect of 18 pyridinium aldoximes on diethylphosphoryl-acetocholinesterase in vitro and the protection against lethal poisoning by ethyl pyrophosphate (TEPP) in mice pretreated with 0.095 m.mole/kg. of these oximes was investigated. Monoximes and dioximes of polymethylenebispyridinium compounds were studied in greater detail since they were up to 22 times more potent than pyridine-2-aldoxime methiodide (2-hydroxyiminomethyl-N-methylpyridinium iodide) in reactivating diethylphosphoryl-acetocholinesterase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
2

Year Published

1961
1961
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 33 publications
1
26
0
2
Order By: Relevance
“…This possibility had to be considered because in higher concentrations both oxidoxime and pralidoxime have a peripheral atropine-like action and antagonize the contractions produced by acetylcholine and carbachol on isolated smooth muscle preparations (Bethe, Erdmann, Lendle & Schmidt, 1957;Hobbiger & Sadler, 1959;Lehmann, 1962;Kuhnen-Clausen, 1970). They may therefore also have a central atropine-like action.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility had to be considered because in higher concentrations both oxidoxime and pralidoxime have a peripheral atropine-like action and antagonize the contractions produced by acetylcholine and carbachol on isolated smooth muscle preparations (Bethe, Erdmann, Lendle & Schmidt, 1957;Hobbiger & Sadler, 1959;Lehmann, 1962;Kuhnen-Clausen, 1970). They may therefore also have a central atropine-like action.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is well known that TMB-4 possesses curare-and atropine-like effects and exerts hypotension in experimental animals. Hobbiger & Sadler (1959) showed that TMB-4 reduced sensitivity of small intestine to acetylcholine in guinea pigs while Bošković & Stern (1963) proved its direct effect on the activity of the rat striated muscle. Results of Lindgren & Sundwall (1960) confirmed its strong parasympatholytic effect in animals not exposed to organophosphates.…”
Section: Discussionmentioning
confidence: 99%
“…This probably is the consequence of a blocking action of the drug on postjunctional nicotinic cholinoceptors (Hobbiger & Sadler, 1959;Fleisher et al, 1960) and comparable to the antagonism of twitch potentiation by tubocurarine (Brown, Dale & Feldberg, 1936).…”
Section: Discussionmentioning
confidence: 99%